Rediseño de procesos de la cadena de suministros del grupo empresarial más activos S.A.S en la ciudad de Tunja (2020)
The proposal made was developed for the company GRUPO EMPRESARIAL MÁS ACTIVOS SAS, in the city of Tunja a company dedicated to the printing of indoor and outdoor advertising, in which 3 phases were carried out, in the first phase the characterization of the chain was carried out of supply of the company, after identifying the times of the processes of the chain of supply by means of stopwatch with return to zero. Subsequently, a failure mode and effect analysis matrix (AMEF) is prepared, where reprocesses and bottlenecks of both workers and machines are found. The second phase develops a mathematical model through the hierarchization process (AHP), in which according to the problems that are evident in the characterization and the result in the weighting of the failure mode and effect analysis matrix (FMEA ), both suppliers and machines were evaluated according to the most important criteria specified by the company manager and thus be able to define the best supplier of supplies and the least efficient machine for the company. The third phase verified the execution of the redesign of the supply chain processes according to the result obtained in the two previous phases, so the modification of the process map was suggested, concurring 3 more links to the supply chain, which confirmed the inclusion of the position of head of supply chain and also identified the least productive machine for the company, with the redesign of these processes and the implementation of the new flow charts, it seeks to mitigate returns, complaints and claims by clients of the company and thus increase both sales and accreditation in the city of Tunja.